Slope Stability Analysis Through the Application of Digital Imagery and Field Validation Using SMR and Q-Slope Methods: A Case Study of Bandar Lampung City, Indonesia - Hilman, Zaki; Edo Kharisma Army; Rezki Naufan Hendrawan (UIR PRESS, 2026)
The investigation is on slope stability in cities such as Bandar Lampung by combining digital imagery from Geographic Information Systems (GIS) and field validation using Slope Mass Rating (SMR) and Q-Slope methods. The research study emphasizes the area of study, which is the city of Bandar Lampung, as the topography is highly diverse and the incidence of landslides is high. The Analytical Hierarchy Process (AHP) employed slope stability assessment by indicating vital parameters such as slope gradient, Normalized Difference Vegetation Index (NDVI), rock type and rainfall, and used AHP to produce a detailed slope stability map, classifying the areas surveyed into three degrees of hazards: low, medium and high. Of these results, low hazard areas occupy an area of 101.56 km², medium hazard areas area covers 52.79 km², and high hazard areas occupy an area of 25.47 km². Field validation using SMR and Q-slope methods at vital sites revealed that most slopes fall into classes of stability, poor to very poor. The dominant types of landslides identified are planar and wedge failures. Based upon the Q-Slope Stability Chart recommended stable slope angles from a range of 42° to 61° were established for different sites. This study shows that these areas are characterized by medium to high hazards, offering steep slopes that have little or almost no vegetational cover, thus greatly enhancing the possibilities of landslides taking place. A Well established correlation between GIS-based mapping and field observation proves how accurate the results would be in the integration of SMR and Q-Slope approaches that would give even better recommendations for slope stabilization measures or landslide mitigations. Findings of the research provide significant information for the matters of urban spatial planning and pro-active disaster risk management in landslide-prone regions of Bandar Lampung.